ANALISIS EKSTERNALITAS INDUSTRI PEMBEKUAN UDANG TERHADAP KONDISI SOSIAL EKONOMI DAN LINGKUNGAN MASYARAKAT DI SEKITAR KAWASAN INDUSTRI TANJUNG BINTANG - Saputri, Alifira Bintang; Prasmatiwi, Fembriarti Erry; Marlina, Lina (Lampung University, 2024)
This study aims to analyze the advantages of the shrimp freezing industry by including the cost of externalities and analyze the industrial externalities of the shrimp freezing industry to the community surround the Tanjung Bintang Sub District Industrial Estate. The analysis method used was quantitative profit and descriptive analysis including social, economic, and environmental aspects to analyze externalities on the society. Data collection was conducted from November to December 2023. The number of respondents were 45 communities around the shrimp freezing industry. The results of this study show that profit exclude externalities cost is IDR145,267,211,244/year, meanwhile profit including externality costs is IDR145,013,188,244/year. The major positive externalities felt by the community around the industry are in the social and economic aspects, while the environmental aspects have less positive impact on the community. The major negative externalities affected the community are environmental aspects and social aspects, while the economic aspects have a small negative impact on the community, and the environmental aspects have a massive negative impact on the community. Key words: externalities, profit, shrimp freezing, socio-economic